A simple and feasible atom-precise biotinylated Cu(i) complex for tumor-targeted chemodynamic therapy. Issue 49 (25th May 2021) - Luo, Bi; Chen, Liguang; Hong, Zhaoguo; You, Xin; Huang, Fu-Ping; Bian, He-Dong; Zhang, Liangliang; Zhao, Shulin
Abstract : A simple and feasible atom-precise biotinylated Cu(i ) complex, which can catalyze H2 O2 overexpressed commonly in the tumor microenvironment to produce ˙OH through a Fenton-like reaction, was prepared and employed as an effective agent for tumor-targeted chemodynamic therapy. Abstract : A simple and feasible atom-precise biotinylated Cu(i ) complex, which can catalyze H2 O2 overexpressed commonly in the tumor microenvironment to produce ˙OH through a Fenton-like reaction, was prepared and employed as an effective agent for tumor-targeted chemodynamic therapy.